The Role of Serum Copper and Iron in Oral Submucous Fibrosis - Master Luquman; Vishnudas Dinesh; Prabhu; M Vidya (Wolters Kluwer Medknow Publications, 2004)
Oral submucous fibrosis (OSMF) is a chronic insidious disease of multifactorial etiology. The habit of chewing arecanut is thought to be one of the most important etiologic factors. Copper and iron are elements in the human body that form part of important enzymes. We estimated the serum copper and iron in patients with OSMF as well as normal controls and discuss the role of these elements in the etiology of OSMF.